Judicial Independence and Political Influence in Modern Democracies - Fathya, Adinda Zahra; Santika, Rani (Politeknik Siber Cerdika Internasional, 2025)
Background: Human rights violations and political interference in judicial systems remain persistent global challenges that undermine accountability, democratic governance, and the rule of law. Armed conflicts, authoritarian governance, and socio-political crises have intensified systematic abuses by both state and non-state actors, while weakening the independence of judicial institutions responsible for upholding justice. Objective: This study aims to examine contemporary human rights violations and assess the effectiveness of international legal mechanisms in addressing these violations, while also analyzing the extent to which political influence affects judicial independence in modern democratic systems. Methods: The research employs a qualitative approach using doctrinal legal analysis and comparative case studies. Data are derived from international legal instruments, judicial decisions, United Nations reports, International Criminal Court (ICC) documents, regional human rights bodies, and scholarly literature published within the last five years. Results: The findings indicate that international legal frameworks provide essential mechanisms for addressing human rights violations; however, enforcement remains inconsistent due to political constraints, jurisdictional limitations, and state non-cooperation. Case studies from Ukraine, Myanmar, Ethiopia, and Venezuela reveal both successes and structural limitations of international legal interventions. Additionally, political interference in judicial appointments, budgetary control, and legislative restrictions significantly undermines judicial independence, contributing to democratic backsliding. Conclusion: The study concludes that strengthening international human rights protection and safeguarding judicial independence require enhanced international cooperation, robust legal frameworks, judicial autonomy, and active civil society engagement. These measures are crucial for ensuring accountability, protecting civil liberties, and promoting democratic resilience in contemporary governance systems.